Optimization of silica glass capillary and rods drawing process. - Wójcik, Grzegorz Michał (Photonics Letters of Poland, 2019)
Diameter fluctuations of silica glass rods and capillaries, during drawing process have been studied. We investigated an influence of drawing conditions on the quality of capillaries and rods. We fabricated two preforms made from different quality material. Fabricated preforms were used to draw microstructured fibers. Full Text: PDF References S. Habib et al., "Broadband dispersion compensation of conventional single mode fibers using microstructure optical fibers", Int. J. Lig. Opt. 124, 3851-3855 (2013) CrossRef A. Ziolowicz et al. "Overcoming the capacity crunch: ITU-T G.657.B3 compatible 7-core and 19-core hole-assisted fibers", Proc SPIE 10130, 101300C (2017) CrossRef T.M. Monro et al. "Sensing with microstructured optical fibres", Meas. Sci. Technol. 12, 854-858 (2001) CrossRef G. Statkiewicz-Barabach et al.,"Hydrostatic Pressure and Temperature Measurements Using an In-Line Mach-Zehnder Interferometer Based on a Two-Mode Highly Birefringent Microstructured Fiber", Sensors 2017, 17, 1648 (2017) CrossRef T. Yoon, M. Bajcsy, "Laser-cooled cesium atoms confined with a magic-wavelength dipole trap inside a hollow-core photonic-bandgap fiber", Phys. Rev. A 99, 023415 (2019) CrossRef A.N. Ghosh et al., "Supercontinuum generation in heavy-metal oxide glass based suspended-core photonic crystal fibers", J. Opt. Soc. Am. B 35, 2311-2316 (2018) CrossRef G. Wójcik et al. "Microbending losses in optical fibers with different cross-sections", Proc. SPIE 10830, 108300H (2018) CrossRef F. Xu, Selected topics on optical fiber technology and applications (IntechOpen 2018) CrossRef